Integrasi Kearifan Lokal dalam Kurikulum Pendidikan Islam untuk Membentuk Karakter Toleransi di Sekolah - Yumnah, Siti (Proceedings of Annual Conference for Muslim Scholars, 2024)
In the era of globalization and advances in information technology, Indonesian society faces increasingly complex challenges related to cultural, religious, and ethnic diversity. This diversity, although a national treasure, also has the potential to cause friction and conflict if not managed properly. Education has a crucial role in shaping the character of the younger generation so that they are able to live harmoniously in this diversity. One approach that can be taken is through the integration of local wisdom in the Islamic education curriculum. The purpose of this article is to discuss the integration of local wisdom in the Islamic education curriculum as an effort to shape a character of tolerance in schools. The research method used is qualitative with a literature study approach, which uses descriptive analysis techniques. The results of the study show that local wisdom applied in the curriculum can increase students' awareness of the importance of respecting cultural and religious differences.